Diaphragm ultrasonography as a monitor in assessing antagonistic effect of sugammadex on rocuronium in patients with Child-Pugh grades A and B - Sun, Yan; Sun, Shujun; Chen, Rui; Shen, Jiwei; Chen, Xiangdong; Lin, Yun; Yao, Shanglong (Frontiers in Medicine, 2024)
Background: Although diaphragm ultrasound can be used for detecting residual neuromuscular blockade post-surgery, there exists notable dearth in contemporary research exploring the correlation between preoperative Child-Pugh classification and the effectiveness of sugammadex in reversing rocuronium-induced blockade as evaluated by diaphragmatic ultrasonography. Methods: This was a prospective, double-blind, non-randomized controlled clinical trial conducted on patients scheduled for laparoscopic liver resection surgery. The participants were categorized into two groups, A and B, based on their preoperative Child-Pugh classification. Prior to anesthesia induction, baseline diaphragm thickness was evaluated using ultrasonography. Throughout the surgical procedure, a deep neuromuscular blockade was maintained with rocuronium. Post-surgery, sugammadex (2 mg/kg) was intravenously administered to patients in both groups upon reaching a train-of-four ratio of 0.2. Diaphragm thickness was assessed at 0, 10, and 30 minutes, as well as 2 hours after extubation, to analyze thickening fractioning (TF) and thickness recovery fractioning (TRF). Results: No significant differences in TF or TRF were observed between the two groups at 0, 10, and 30 minutes, as well as 2 hours after extubation. Furthermore, there were no significant variances in hemodynamic stability following sugammadex administration. However, patients in the Child-Pugh B group experienced a significantly prolonged time from sugammadex administration to tracheal extubation (19±8.0 min vs. 11±6.1 min) and an extended post-anesthesia care unit stay (123±28.3 min vs. 103±26.0 min) compared to those in the Child-Pugh A group. Conclusions: The preoperative Child-Pugh grades may not exhibit a significant association with the reversal effect of sugammadex on rocuronium, as evaluated through diaphragmatic ultrasonography. Trial registration: Registered in the ClinicalTrials.gov (NCT05028088) on July 18, 2021.